Переваги систем електричного опалення з нічним акумулюванням теплоти в умовах України - Андрющенко, Анатолій Михайлович; Нікульшин, Володимир Русланович; Денисова, Алла Євсіївна (НТУ "ХПІ", 2018)
Мета дослідження - розробка системи електричного опалення з нічним акумулюванням теплоти та обґрунтування її енергозберігаючого характеру в порівнянні з іншими можливими варіантами опалення. Методика заснована на сучасних стандартах України і включає наступні основні допущення: коефіцієнт корисної дії електричного котла приймається рівним 100 %; залежність опалювального навантаження будівлі від зовнішньої температури вважається лінійною; для всіх розрахункових варіантів опалення, що використовують різні енергетичні ресурси, режим роботи системи опалення відстежує погодні умови відповідно до температури зовнішнього повітря. Методика передбачає визначення основних технічних характеристик системи з урахуванням можливості включення електричного бойлера в денний час на половину розрахункового навантаження. На основі запропонованого методу була розроблена розрахункова програма для визначення щомісячного теплоспоживання будівлі і розрахунку вартості опалення при використанні різних енергетичних ресурсів. Ця програма також дозволяє зіставляти вартості централізованого теплопостачання як по теплоті, що спожита, так і при оплаті за величиною опалювальної площі. Вперше наведені метод і програма розрахунку систем електроопалення з нічним акумулюванням теплоти, що враховують діючі стандарти України та дозволяють визначати основні технічні характеристики системи, а також розраховувати вартості опалення при використанні різних видів енергетичних ресурсів. Використання запропонованої методики дозволяє проектувати енергозберігаючі системи електричного опалення з нічним акумулюванням теплоти. Наведено чисельний приклад для реальних погодних умов м. Києва. Доведено, що термін окупності переходу на електроопалення для варіанту заміни централізованого теплопостачання з оплатою за спожиту теплоту складає менше, ніж 3 роки, для варіанту заміни централізованого теплопостачання з оплатою за опалювальну площу складає менш,

To develop electrical heating systems with night heat accumulation and to prove its advantages comparable with others possible variants of heating. We have purposed a methodology which is based on the current Standards of Ukraine and included few main assumptions: the efficiency of the electric boiler is assumed equal 100 %; the dependence of the building heating load on the outside temperature is linear; all the variants of different energy resources calculating for the system operating correspond to the adequate (depending on weather) regulation. Methodology allows to determine the main technical characteristics of the system taking into account the possibility of switching on the electric boiler in the daytime using the half-loading. On the base of suggested methodology was developed the calculation program for determine the monthly consumption of heat by the building and estimate the cost of heating using different energy sources. This program also allows to compare the payment for centralized heat supply services at the tariff for the consumed heat with a payment for the heated area tariff. We have obtained a method for electrical heating systems with nightheat accumulation calculation. Method bases on the current Standards in Ukraine and allows to determine the main technical characteristics of the system taking into account the possibility of switching on the electric boiler in the daytime. On the base of suggested method was developed the calculation program for determine the monthly consumption of heat by the building and estimate the cost of heating using different energy resources. This program also allows to compare the payment for centralized heat supply services at the tariff for the consumed heat with a payment for the heated area tariff. For the first time we have suggested methodology and developed the calculation program for electrical heating systems with night heat accumulation which is based on the Ukrainian Standards and allows to determine the monthly consumption of heat by the building and estimate the cost of heating using different energy sources. We have developed a method and calculation program which allows to design the energy saving electrical heating systems with night heat accumulation. We have demonstrated on the numerical example for the real weather conditions of Kyiv city the economical advance of using electric heating with night heat accumulation comparable with all others options (centralized heat supply, gas heating, pellet heating). For December 2017 tariffs in Ukraine, the cost of electrical heating with night heat accumulation are two times lower than in the case of centralized heat supply with payment for consumed heat. We have proved that the refund period for implementation of electrical heating systems with night heat accumulation instead of centralized heat supply services at the tariff for the consumed heat is less than 3 years, and for centralized heat supply services at the tariff for the heated area tariff is less than 1 year.
Advantages of electrical heating systems with night heat accumulation in Ukrainian conditions
Keywords: енергозбереження; електроопалення; енергетичні ресурси; спожиживання теплоти; energy saving; different energy resources